Distributed consensus‐based routing protocol with multiple mobile sinks support for wireless sensor network. (10th March 2021) - Khalid, Nor Azimah; Bai, Quan; Al‐Anbuky, Adnan
Abstract: Non‐uniform node distribution in a randomly deployed network causes inefficient routing when some abnormality or events at certain parts of the network cannot be detected due to a coverage hole problem. Existing works to improve routing efficiency in randomly deployed network utilise mobile sink to prolong nodes lifetime is either centred around the static sink or movement through random patterns. Few works had considered multiple mobile sinks to route packets in such network distribution. In fact, important aspect such as collaborations among mobile sinks is not well considered, where the decision made by each mobile sink in most existing approaches tend to maximise the individual sink's utility rather than benefiting wider parts of the network. Thus, a decision based on consensus may benefit more parties and eventually lead to better decision. A distributed collaboration mechanism may assist nodes mobility in improving routing efficiency. Thus, the authors proposed the consensus‐based routing protocol, which aims to improve routing efficiency in randomly deployed network, by deciding relocation of mobile sinks based on coverage factor, in order to reduce energy consumption, providing more balance sinks distribution and better network coverage. Simulation results show good performances of proposed approach in terms of nodes lifetime, energy consumption, delay, packet delivery ratio and coverage hole, compared to other existing protocols.